De la violence au cadavre : étude d’une mort genrée - Anaelle Lahaeye (Les Cahiers de l'École du Louvre)
In 1856 Allan Edgar Poe wrote: “The death of a beautiful woman is, unquestionably, the most poetical topic in the world”. Although this statement may seem strange nowadays, it attests the high regard in which the motif of a beautiful dead woman was held. In the 19th century, this motif pervaded cultural works to the extent of creating an imaginative universe seen both in fashion reviews and on the walls of the Salon. This success is all the more surprising because it ran counter to the evolution of other works that featured dead bodies. This persistence derives in part from the gendered representation of corpses, which renders the motif suitable for expressing stereotypes and their implications regarding different relationships to violence. Beautiful dead women are therefore a perfect example for questioning how art is a space of both materialisation and the transcension of an era’s systems of thought.